Rome and the Near Eastern Kingdoms and Principalities, 44-31 BC - Wijlick, Hendrikus A.M. van, author.
1 online resource.
Keywords: “The study presents a critical analysis of the political relations between Rome and Near Eastern kingdoms and principalities during the age of civil war from the death of Julius Caesar in 44 to Mark Antony's defeat at Actium in 31 BC. By examining each bilateral relationship separately, it argues that those relations were marked by a large degree of continuity with earlier periods. Circumstances connected to the civil war had only a limited impact on the interstate conduct of the period despite the effects that the strife had on Rome's domestic politics and the res publica. The ever-present rival Parthia and its external policies were more influential in steering the relations between Rome and Near Eastern powers“--